Analisis Pengaruh Kualitas Pelayanan TerhadapKepuasan Konsumen(Studi Kasus Pada Kedai Matmoen Di Kab. Boyolali) - Nugroho, Febrianto Catur; , Muzakar Isa, SE., M.Si (2017)
ABSTRACTION This study aims to look at the impact of service quality to the customer satisfaction (A case study on Matmoen shops in the district. Boyolali). Samples taken as many as 100 respondents who had come to shop Matmoen Boyolali. The analysis tool uses SPSS software to test the validity and reliability, and multiple regression test. Results found shows that partial tangible, assurance and empathy significant effect on customer satisfaction, while reliability and responsiveness but not significant effect on customer satisfaction. Simultaneously tangible, assurance, empathy, reliability and responsiveness significantly influence consumer satisfaction shops Matmoen Boyolali. In the variable determinant coefficient x can explain y 66.4 and the rest influenced by other factors at 33.6%. Keywords: Tangible, Assurance, Emphaty, Reliability, Responsiveness, Costumer Satisfaction.